Flood detector / Muhammad Atiq Aminudin and Mohamad Helmi Akmal Kamarul Arifin - Aminudin, Muhammad Atiq; Kamarul Arifin, Mohamad Helmi Akmal (2015)
The flood detector is designed to see the efficiency of water detection that leakage from the human house that will harmful to their furniture and also the electric devices inside their house. Other than that, several problem about the flood in certain house for example a water tube broke in middle of the night without the occupant notice and it will cause many damage in the house because of the water. Other than that, wasting of water also one of the problem that encourage we to accomplished this project such as the water pipe in the bathroom damage or forgotten to close it that will waste many water. The calculated parameters have been optimized using some software such as MPLAB that function as to write any type of program that can be transferred into machine code that can verify in PIC ( Programmable Integrated Circuit ) and personalize into the hardware. Before that, we also use a software names PROTEUS that the program function as a simulation before we simulate in hardware. From this software we can make some troubleshoot and detect our problem that easy and fast to overcome it. We also should get the wanted result that the output of project is LED green and LED red function and piezo buzzer also should function. It is observed that the gain is improved the problem of human being in their life.